Degradation analysis of polymeric pipe materials used for water supply systems under various disinfectant conditions. (March 2022) - Khan, Imtiaz Afzal; Lee, Kang Hoon; Lee, Yong-Soo; Kim, Jong-Oh
Abstract: Addition of chlorine dioxide (ClO2 ) or sodium hypochlorite (NaOCl) as a disinfectant in municipal water distribution systems is a common practice to deactivate micropollutants, but their impact on the pipe material with long-term exposure has not been discussed in detail. In this study, accelerated aging experiments were conducted for evaluating the oxidation of high-density polyethylene (HDPE), low-density polyethylene (LDPE), unplasticized polyvinylidene chloride (UPVC), and high-impact polyvinylidene chloride (Hi-PVC) pipes. The pipes were immersed in deionized (DI) water, ClO2, and NaOCl (2 mg/L, 5 mg/L, and 10 mg/L doses) for 1200 h of aging at 40 °C. The variations in the pipes structural, thermal, and mechanical characteristics were systematically investigated by attenuated total reflectance-Fourier transform infrared radiation (ATR-FTIR), X-ray photoelectron spectroscopy (XPS), differential scanning calorimetry (DSC), and a universal testing machine (UTM). The formation of carbonyl groups due to methylene groups (C–C/C–H) oxidation resulted in an increased carbonyl index (CI) of the material exposed to accelerated aging conditions. Moreover, the XPS and ATR-FTIR results elucidated that the oxidation patterns under the exposure conditions followed from ketone/aldehyde formation to carboxylate groups (carboxylic acid/ester). The pipes were more vulnerable to the ClO2 compared to the DI water and NaOCl solution exposure. The increase in crystallinity and the decrease in oxidation induction time (OIT) of the pipe materials confirmed that the loss of stabilizer and changes in the chain alignment resulted in chain secession, loss of ductility, and lower percent elongation at break. Furthermore, results also elucidated that oxidative stability of the HDPE/UPVC was greater than that of the LDPE/Hi-PVC under disinfectant exposure regardless of the concentration and duration. Graphical abstract: Image 1 Highlights: Chlorine dioxide effects more severely to pipes materials. Oxidation stability of HDPE/UPVC > LDPE/Hi – PVC. Degradation follows the formation of Ketones/aldehydes .→ carboxylate groups PVC pipes mechanical strength were susceptible under chemical attack.